2010
DOI: 10.1016/j.bbadis.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosiglitazone on intramyocellular lipid accumulation in Psammomys obesus

Abstract: Since smaller IMCL droplets are associated with improvements in insulin sensitivity, we propose that this may be an important mechanism by which rosiglitazone affects glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…It is quite well established that the accumulation of intramyocellular lipids is strongly associated with highfat diet intervention, and several studies suggested that the activation of PPARc (rosiglitazone or pioglitazone) reduces this toxic accumulation of lipids in muscles (Hockings et al 2003, Jucker et al 2003, Ye et al 2004, Molero et al 2010. We found that, irrespective of diet, rosiglitazone induces fibrespecific (soleus and red gastrocnemius) accumulation of intramuscular lipids (FFA and TAG).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…It is quite well established that the accumulation of intramyocellular lipids is strongly associated with highfat diet intervention, and several studies suggested that the activation of PPARc (rosiglitazone or pioglitazone) reduces this toxic accumulation of lipids in muscles (Hockings et al 2003, Jucker et al 2003, Ye et al 2004, Molero et al 2010. We found that, irrespective of diet, rosiglitazone induces fibrespecific (soleus and red gastrocnemius) accumulation of intramuscular lipids (FFA and TAG).…”
Section: Discussionmentioning
confidence: 51%
“…It is quite well established that the accumulation of intramyocellular lipids is strongly associated with highfat diet intervention, and several studies suggested that the activation of PPARc (rosiglitazone or pioglitazone) reduces this toxic accumulation of lipids in muscles (Hockings et al 2003, Jucker et al 2003, Ye et al 2004, Molero et al 2010. In the aforementioned studies, the proposed mechanism of PPARc actions appeared to be related to the sequestration of lipids away from skeletal muscle to adipose tissue with secondary decrease in serum FAs and subsequent reduction in an intramuscular lipid content (Kliewer et al 1994, Jucker et al 2003, Ye et al 2004, Molero et al 2010. However, there is an increase body of evidence showing also rosiglitazone-induced enhancement of skeletal muscles' insulin sensitivity, with no evident change in intramuscular lipid pool(s) (Mayerson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…triggers new LD formation during adipogenesis ( 59 ). However, prolonged treatment is known to be antiobesogenic, to promote lipolysis, and to block LD fusion, resulting adipocytes containing small LDs ( 60,61 ).…”
Section: Comparison Of Lipid-quant With Standard Methodsmentioning
confidence: 99%